Evaluation of microlysimeters used in turfgrass evapotranspiration studies with the dual-probe heat-pulse technique - Bremer, Dale J. (My University, 2009)
Microlysimeters (ML) are commonly used in turfgrass evapotranspiration (ET) studies. No standard exists for ML which has resulted in multiple designs that may affect soil moisture. The effects of ML design on volumetric soil water content ([Greek letter theta subscript v]) were investigated using the dual-probe heat-pulse (DPHP) technique. DPHP sensors were installed at 5, 15, and 25 cm in the ambient soil profile and in 3 designs of ML: 1) 15 cm diam. x 30 cm, mesh base, soil fill (MSL); 2) 15 cm diam. x 30 cm, plexiglass base (one drainage hole), soil fill (PSL); 3) 10 cm diam. x 20 cm, mesh base, soil (intact cores) (MSNL). Sleeves and a 5 cm layer of gravel were placed in MSL and PSL. DPHP estimates of [Greek letter theta subscript v] revealed that soils consistently dried faster in MSL and PSL than in the ambient profile, probably because of higher LAI and biomass in MSL and PSL than in surrounding turf, limitations of roots to extract soil water only from ML, and evaporation through open bases. In MSNL, [Greek letter theta subscript v] was similar to but may have been in hydraulic contact with ambient soils. Correlation was good between [Greek letter theta subscript v] determined by DPHP and by gravimetric methods; DPHP sensors on average (all ML) measured [Greek letter theta subscript v] to within 0.025 m[superscript 3] m[superscript minus 3] of gravimetric estimates. ET estimates varied significantly among ML and were strongly correlated to LAI and aboveground biomass (r=0.85). Results suggest that establishment/maintenance of similar LAI and biomass between ML and surrounding turf may be more important than ML design in providing accurate ET estimates, and bases should be sealed during ET measurements to prevent hydraulic contact with soil, drainage, or evaporation through bases.
Keywords: Lysimeters; Lysimeter design; Evapotranspiration; Soil moisture sensors